Tackling infiltration in paediatric glioma using histone deacetylase inhibitors, a promising approach. (31st January 2018) - Jackman, Lara; Ago, Emmanuel; Boissinot, Marjorie; Grigg, Ronald; Esteves, Filomena; Morton, Ruth; Short, Susan; Brüning-Richardson, Anke
Abstract: INTRODUCTION: Targeting the migratory behaviour of invading cells in high grade paediatric gliomas represents an attractive combination therapy with current treatment options. Migration involves highly regulated microtubule dynamics that have been linked to the acetylation status of tubulin. MI192 is a selective histone deacetylase inhibitor that has previously been shown to modulate tubulin acetylation. METHOD: The effect of MI192 on cell migration was investigated in two paediatric high grade glioma cell lines, SF188 and KNS42. Live cell imaging of 2D cell monolayers and 3D spheroid invasion assays were performed to assess the effect of MI192 on cell migration as well as immunofluorescence on 2D cell monolayers to measure changes in acetylated tubulin, proliferation, stemness and apoptosis. RESULTS: In SF188, compared to the untreated control, MI192 demonstrated anti-migratory effects in 3D spheroid assays. This was associated with elevated levels of tubulin acetylation by immunofluorescence and corresponded with distinct differences in cellular movement by live cell imaging. These effects were not due to increased rates of apoptosis. In KNS42, MI192 did not have anti-migratory effects in live cell imaging 2D experiments. In addition, in 3D only the highest concentration of MI192 (pre-determined to have an effect on cell viability) reduced cell migration. This corresponded to reduced Ki67 levels, increase in apoptosis and loss of stemness markers on immunofluorescence. CONCLUSION: SF188 and KNS42 exhibited different responses after exposure to MI192. SF188 was the more sensitive, with anti-migratory effects observed both in 2D and 3D, which were not a consequence of apoptosis. For KNS42, the main effect of MI192 was to push the cells towards differentiation and apoptosis, another previously described effect of this drug. These preliminary findings warrant further investigations into the mechanisms downstream of MI192 and its use as an anti-migratory and/or pro-differentiating agent.